-x+3-3x=-13

Simple and best practice solution for -x+3-3x=-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -x+3-3x=-13 equation:


Simplifying
-1x + 3 + -3x = -13

Reorder the terms:
3 + -1x + -3x = -13

Combine like terms: -1x + -3x = -4x
3 + -4x = -13

Solving
3 + -4x = -13

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -4x = -13 + -3

Combine like terms: 3 + -3 = 0
0 + -4x = -13 + -3
-4x = -13 + -3

Combine like terms: -13 + -3 = -16
-4x = -16

Divide each side by '-4'.
x = 4

Simplifying
x = 4

See similar equations:

| b-3=2 | | x-4x-5=0 | | 8x^2-7x+4=0 | | 9p^2-17p-2= | | -0.67(5p-16)=10 | | 8+x=24 | | 9(z-1)+2z+16=62 | | 5=-9+x | | 7=-0.75x | | a+1=-1 | | -26=m-16 | | 6x-8=112 | | 3(2x-8)-(3x+2)=-15 | | 7500.00+155.00*1.00x=92440 | | 11x-21=89whatisx | | -0.61+m=0.3 | | h+21=-50 | | x+y-8xy=x | | 2(x-3)+3(2x-4)=2(4x+1)-3(4x-1) | | -6v+3v=3 | | f+47=100 | | 2x-3x=7 | | 19+g=32 | | X-(-22)=-8 | | 0.4b+1=-11 | | 2x+4=-16 | | 3x+15=-42 | | -10=3+c | | 3(2x-3)=11-x | | 0.00676-0.4169+1=0 | | b+61=27 | | 3m-2(m+3)=m |

Equations solver categories